Liability of online marketplaces for consumer losses in online transactions as reviewed under law number 8 of 1999 on consumer protection - Tohadi, Tohadi; Sianturi, Gabriel; Betani, Cintya; Astari, Patricia Divani Anugrah; Palka, Arova Julia; Pahlevi, Mohamad Reza (Priviet Social Sciences Journal, 2026)
The rapid expansion of online marketplace platforms in Indonesia has fundamentally reshaped consumer transaction practices, while simultaneously increasing the incidence of consumer losses arising from non-conforming goods, counterfeit products, delivery failures, and fraudulent schemes. Recent reports and publicly documented cases have revealed persistent vulnerabilities in marketplace transaction systems, raising critical questions regarding the legal responsibility of marketplaces to protect consumer rights. Despite the growing relevance of this issue, existing studies largely focus on seller liability or contractual relationships, leaving the role and accountability of marketplaces under Indonesian Consumer Protection Law insufficiently examined. This study aims to analyze the liability of online marketplaces for consumer losses in electronic transactions under Law Number 8 of 1999 on Consumer Protection. Employing a normative juridical research method, this study applies a statutory and conceptual approach by examining consumer protection legislation, civil law principles, and relevant legal doctrines, supported by scholarly literature and documented cases. The findings demonstrate that marketplaces qualify as business actors and therefore bear legal obligations under Articles 4, 7, and 19 of the Consumer Protection Law, including the duty to provide accurate information, ensure transaction security, and offer compensation for consumers’ losses. However, the implementation of such liability remains largely dependent on internal marketplace policies, which often limit the effectiveness of consumer remedies. This study contributes to the literature by clarifying the legal position of marketplaces as responsible actors in online transactions and strengthening the normative foundation for enhanced consumer protection in Indonesia’s digital commerce ecosystem.